The hole transport mechanism of MoOx/a-Si: H(i)/n-Si heterojunction photovoltaic devices: the source of the 'S-shaped' behavior. (28th July 2020) - Gao, M; Chen, D Y; Du, H W; Wu, K J; Meng, F Y; Ma, Z Q
Abstract: For the purpose of introducing a high work-function layer to improve the implied voltage in asymmetric silicon-based heterojunction photovoltaic devices, molybdenum oxide (MoOx, 0 < x < 3) is applied to the device. However, besides the role of extracting holes on one side, another singularity behavior presented itself in the nonequilibrium state, i.e. a worsened photovoltaic peformance (an 'S-shape') of current density versus voltage (J–V) was revealed with an inappropriate chemical state of the MoOx film. The source of the 'S-shaped' behavior of an MoOx /a-Si: H(i)/n-Si heterojunction device was co-analyzed by x-ray photoelectron spectroscopy with depth profiling, ultraviolet photoelectron spectroscopy, current density-voltage representation, a minority carrier lifetime survey and automat for simulation of heterostructures software simulation. It was found that an amorphous SiOx interlayer was spontaneously formed during the deposition of MoOx film onto a-Si: H(i)/n-Si substrate, blocking the transport of holes. The decrease in the work-function of the MoOx layer is attributed to an oxidation reaction at the MoOx /a-Si: H(i) boundary zone, which results in the decline of hole selectivity. A rising O/Si ratio in the SiOx interlayer induces an augmentation of valence band offsets, which could be the best interpretation of the 'S-shaped' response, because of a barrier that hinders the thermionic emission of holes. Meanwhile, the thicker (>4 nm) SiOx layer leads to a lower tunneling probability for holes. The characteristic analysis of the MoOx /a-Si: H(i)/n-Si heterojunction device deepens the understanding of the hole transport mechanism of the device.